Design and Analysis of PtSe2 and Blue Phosphorus/MoS2 Heterostructure-Based SPR Biosensor - Chowdhury, Abu Shahid; Islam, Md. Alimul; Islam, Md. Sherajul; Dey, Biswajit; Park, Jeongwon (ACS applied optical materials, 2024)
Biosensors using surface plasmon resonance (SPR) have emerged as effective tools for accurate and instantaneous sensing applications. Nevertheless, optimizing sensor configurations continues to be of utmost importance to attain dependable sensing capabilities. This work presents an intriguing design structure that integrates conventional SPR technology with PtSe2 and blue phosphorus–MoS2 heterostructure, resulting in an improved and adaptable sensing technology. The finite-difference time-domain (FDTD) method was used to model and design the prospective sensor. The proposed design has notable attributes, such as an extraordinarily narrow full width at half-maximum (FWHM) of 8.23°, small detection accuracy of 0.1215, an extraordinary sensitivity of 240.54°/RIU, and an outstanding quality factor of 29.23 RIU–1. Significantly, this sensor has a sensitivity that is 3.2 times higher than that of traditional gold-based SPR sensors. In addition, the sensor provides a broad observable range of refractive indices, ranging from 1.33 to 1.36. The broad spectrum of this detection system allows for the identification of diverse ambient chemicals, such as alcohol, ethanol, and water, as well as biomolecules, including urine, glucose, and DNA hybridization. These results represent a significant stride forward for SPR biosensors, allowing for the creation of high-performance sensing systems with a wide range of potential uses.